Autoantibodies to domain 1 of beta 2 glycoprotein I determined using a novel chemiluminescence immunoassay demonstrate association with thrombosis in patients with antiphospholipid syndrome. (July 2016) - Mahler, M; Albesa, R; Zohoury, N; Bertolaccini, M L; Ateka-Barrutia, O; Rodriguez-Garcia, J L; Norman, G L; Khamashta, M
Introduction: Antibodies to the domain 1 of beta 2 glycoprotein I (β2 GPI–D1) have been suggested as a risk marker for thrombosis in patients with the antiphospholipid syndrome (APS). This cross-sectional study aimed to analyze the clinical utility of a novel chemiluminescence assay for the detection of anti-β2 GPI–D1 antibodies. Patients and methods: Sera collected from patients with primary or secondary APS ( n = 106; 72 with and 34 without history of thrombosis) and controls ( n = 272) were tested for anti-β2 GPI–D1 IgG by chemiluminescence assay (QUANTA Flash) and by two anti-β2 GPI IgG assays (QUANTA Lite and QUANTA Flash β2 GPI IgG). Results: Anti-β2 GPI–D1 IgG titers were significantly higher in patients with thrombosis ( P = 0.0032) than those without. At the cut-off of 20 units, which yielded a 99.5% specificity, 24 of 72 (34.9%) patients with thrombosis and four of 34 (11.8%) without thrombosis were anti-β2 GPI–D1 IgG positive (odds ratio, OR = 4.0). By further optimizing the cut-off specifically for correlation with thrombosis, 20.8% of the patients with thrombosis and 2.9% of the patients without thrombosis were positive (OR = 8.7). The ORs were significantly lower for antibodies to the full-length β2 GPI by either the chemiluminescence assay or ELISA. Using the anti-β2 GPI chemiluminescence assay, the OR was 2.3 (recommended cut-off of 20 CU) or 4.1 (optimal cut-off 164.6 CU). Using the anti-β2 GPI ELISA, the OR was 2.7 (recommended cut-off of 20 units) or 3.7 (optimal cut-off 7.6 units). Conclusion: These data indicate that anti-β2 GPI–D1 IgG are present more frequently and in higher titers in APS patients with thrombotic complications than in those without.The novel β2 GPI–D1 chemiluminescence assay appears to be superior to full-length β2 GPI assays for the risk assessment of thrombotic events in APS patients.